Optimization of the Management of Samapta Patrols to Prevent Motor Vehicle Theft in the Jurisdiction of Brebes Police Resort - Burhan, Annisa Zita Pratiwi (Advances in Police Science Research Journal, 2024)
The rise of vehicle theft that is troubling the community causes disruption of public-order and security. Police as protectors of the community are trying to maintain public-order and security through the samapta patrol. Management Samapta patrols is very important in preventing vehicle theft. This research aims to describe the management of samapta patrol to prevent motor vehicle thefts, to describe the organizational resources of Samapta Unit and to identify the factors that affect the samapta patrol in preventing vehicle thefts in Brebes Police. The theories used in this study are management theories with their elements and SWOT theories. Furthermore, the concept used is optimization, patrol, and vehicle theft. This research was conducted using qualitative approach with field research. Data were collected through interviews, observations, and document studies. The results of the study showed that the cases of vehicle thefts are the most prominent ones in Brebes Police. Patrol management of Samapta Unit in preventing vehicle theft is not optimal yet because deficiencies still exist at every stage. The factors that can affect the implementation of Samapta Unit patrols consist of internal factors and external factors that support and hinder its implementation. Therefore, it is necessary to optimize the management of the Samapta Unit's patrol implementation to prevent criminal acts of motorized vehicle theft in the jurisdiction of the Brebes Police.